The Stubborn Persistence of Sex Segregation - Cohen, David S. (Columbia Journal of Gender and Law, 2011)
Almost fifty years ago, Congress began protecting against sex discrimination in federal statutory law. Almost forty years ago, the Supreme Court expanded constitutional law to include protection from discrimination based on sex. Since then, guarantees against sex discrimination have proliferated in federal and state law, and societal norms of sex equality have become entrenched. Yet, we still live in a society that is highly segregated by sex. And not just sex segregation in the same way race segregation persists-the de facto race segregation that persists, despite de jure segregation disappearing decades ago, in patterns of housing, education, employment, relationships and other areas of life. Rather, the sex segregation most people encounter on a daily basis is sex segregation that is required by rule. Despite its predominance, the persistence of sex segregation has been an under-studied and under-theorized phenomenon in the United States. Legal scholars have studied particular instances of sex segregation, such as in education, the military, restrooms and athletics. However, scholars have paid very little attention to the topic generally, in all of its manifestations. This Article forms the foundation of a multi-part project that will analyze sex segregation as a systemic issue by exploring the contours of modem American sex segregation and what this phenomenon means for law, feminism, gender and identity. In this Article, I set the stage for the entire project by providing a systematic account of sex segregation in America. In addition, I situate this empirical data within a broader doctrinal and theoretical framework. In a second article, I analyze sex segregation and its implications for masculinity, arguing that sex segregation in its many forms contributes to constricting notions of masculinity that lead to the subordination of women as well as of men who do not conform to traditional notions of masculinity. In a related book chapter, 1 have also begun to analyze the deleterious consequences sex segregation has for transgendered, intersexed and gender variant individuals. I plan to more fully explore this issue in the future, including sex segregation’s important implications for women, people of color and society as a whole. My goal in this piece and the others that will build upon it is to provide a comprehensive framework for thinking and dealing with the problem of sex segregation.